La fuerza obligatoria del Contrato - Ghestin, Jacques (Pontificia Universidad Católica del Perú, 2015)
The author begins this article focusing on how historically the contract has reached such binding; from its philosophical origins, through his word to a matter of loyalty to Christian morality; to attribute the quality of certainty as contribution to the economy and become an indispensable legal instrument of forecasting for relations between individuals. Finally, in the second part of this article, essential applications mainly include contract between both parties and to third parties, also seeking the role of judge.

El autor inicia el presente artículo centrándose en cómo históricamente el contrato ha alcanzado dicha fuerza obligatoria; desde sus orígenes filosóficos, pasando por la palabra empeñada a una cuestión de fidelidad en la moral cristiana; hasta atribuirle la calidad de certeza como aporte en la economía y convertirse en un instrumento jurídico indispensable de previsión para las relaciones entre los particulares. Finalmente, en la segunda parte de este artículo, destacan principalmente las aplicaciones esenciales del contrato tanto entre las partes como frente a terceros, tratando también el rol del juez.
The binding force of the Contract
Keywords: Contract; Obligations; Contractual Liability; Contractual Freedom; Concurrence Of Wills; Contrato; Obligaciones; Responsabilidad Contractual; Libertad Contractual; Acuerdo de Voluntades; https://purl.org/pe-repo/ocde/ford#5.05.00